Aspectual classification of mandarin Chinese verbs : a perspective of scale structure - Peck, JeeYoung (2014)
Previous studies of the lexical aspect of verbs following Vendler (1967) cannot account for verbs of degree achievements (Dowty 1979, Hay et al. 1999, among others). Building on recent studies on ”scale structure” (Hay et al. 1999, Rappaport Hovav & Levin 2010, among others). We introduce a new aspectual feature [±scale] into the traditional Vendler system in order to more comprehensively account for a wider range of verbs. By analyzing verbs/verbal compounds from Mandarin Chinese and following the scalar approach, we propose six aspectual classes that are needed not only to adequately accommodate degree achievements, but also to provide a fuller account of all the verbs. This scalar approach can be applied to the aspectual classification of natural languages in general.